Education System for Indigenous Communities: A Review of Social Ecology - Wantik, Laorens; Laksmono, Bambang Shergi; Lefaan, Avelinus; Lumintang, Onnie M. (Indonesian Journal of Advanced Research, 2024)
This research aims to integrate traditional knowledge in the formal education system of indigenous communities, improve access, and preserve local culture. The methods used involve interviews, observations, and reviews of local education policies. Local governments and indigenous community leaders were involved in the reform process to develop a bilingual curriculum that respects local languages and traditions. The results of the study show that socially and ecologically relevant education can increase student participation, strengthen cultural identity, and support environmental sustainability. The policy implications underscore the importance of collaboration between the government and communities in sustainable indigenous education planning.